Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
a) 1/4(x-3)+2=1/5
1/4.(x-3) = 1/5-2
1/4.(x-3) = -9/5
x-3 = (-9/5):1/4
x-3 = -36/5
x = -36/5+3
x= -21/5
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\frac{2}{3}\left(x-1\right)-x-\frac{3}{4}=1\)
<=> \(\frac{2}{3}x-\frac{2}{3}-x-\frac{3}{4}=1\)
<=> \(-\frac{1}{3}x-\frac{17}{12}=1\)
<=> \(-\frac{1}{3}x=\frac{29}{12}\)
<=> \(x=-\frac{29}{4}\)
\(\frac{5}{6}\left(x+2\right)-x-\frac{1}{2}=\frac{1}{3}\)
<=> \(\frac{5}{6}x+\frac{5}{3}-x-\frac{1}{2}=\frac{1}{3}\)
<=> \(-\frac{1}{6}x+\frac{7}{6}=\frac{1}{3}\)
<=> \(-\frac{1}{6}x=-\frac{5}{6}\)
<=> \(x=5\)
học tốt
![](https://rs.olm.vn/images/avt/0.png?1311)
a) -4/5 + 5/2x = -3/10
5/2x = -3/10 + 4/5
5/2x = 1/5
5/2x = 1/2
x = 1/2 : 5/2
x = 1/5
b) 4/3 + 5/8 : x = 1/12
5/8x = 1/12 - 4/3
5/8x = -5/4
5 = -5/4.8x
5 = -10x
5/-10 = x
-1/2 = x
x = -1/2
c) (x - 1/3)(x - 2/5) = 0
x - 1/3 = 0 hoặc x - 2/5 = 0
x = 0 + 1/3 x = 0 + 2/5
x = 1/3 x = 2/5
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left(\frac{2}{5}\right)^2+5\frac{1}{2}:\left(4,5-2\right)-0,2\)
\(=\frac{4}{25}+\frac{11}{2}:\frac{5}{2}-\frac{1}{5}\)
\(=\frac{4}{25}+\frac{11}{2}.\frac{2}{5}-\frac{1}{5}\)
\(=\frac{4}{25}+\frac{11}{5}-\frac{1}{5}\)
\(=\frac{4}{25}+\frac{55}{25}-\frac{5}{25}\)
\(=\frac{54}{25}\)
a) Đề sai
b) \(\left|x+\frac{4}{5}\right|=\frac{1}{7}\)
\(\Rightarrow\orbr{\begin{cases}x+\frac{4}{5}=\frac{1}{7}\\x+\frac{4}{5}=\frac{-1}{7}\end{cases}}\Rightarrow\orbr{\begin{cases}x=\frac{1}{7}-\frac{4}{5}\\x=\frac{-1}{7}-\frac{4}{5}\end{cases}\Rightarrow\orbr{\begin{cases}x=\frac{5}{35}-\frac{28}{35}\\x=\frac{-5}{35}-\frac{28}{35}\end{cases}\Rightarrow}\orbr{\begin{cases}x=\frac{-23}{35}\\x=\frac{-33}{35}\end{cases}}}\)
Vậy \(x=\frac{-23}{35}\)hoặc \(x=\frac{-33}{35}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a,\frac{-3}{2}-2x+\frac{3}{4}=-1\)
\(\frac{-3}{2}-2x=-1-\frac{3}{4}\)
\(\frac{-3}{2}-2x=\frac{-7}{4}\)
\(2x=\frac{-7}{4}+\frac{-3}{2}\)
\(2x=\frac{-13}{4}\)
\(x=\frac{-13}{4}:2\)
\(x=\frac{-13}{4}.\frac{1}{2}\)
\(x=\frac{-13}{8}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a)\(x+\frac{1}{3}=\frac{3}{4}\)
\(\Rightarrow x=\frac{3}{4}-\frac{1}{3}\)
\(\Rightarrow x=\frac{5}{12}\)
b)\(x-\frac{2}{5}=\frac{5}{7}\)
\(\Rightarrow x=\frac{5}{7}+\frac{2}{5}\)
\(\Rightarrow x=1\frac{4}{35}\)
c)\(-x-\frac{2}{3}=-\frac{6}{7}\)
\(\Rightarrow-x=-\frac{6}{7}+\frac{2}{3}\)
\(\Rightarrow-x=-\frac{4}{21}\)
\(\Rightarrow x=\frac{4}{21}\)
d)\(\frac{4}{7}-x=\frac{1}{3}\)
\(x=\frac{4}{7}-\frac{1}{3}\)
\(\Rightarrow x=\frac{5}{21}\)
`a, -3x - 3/4 = 6/5`
`=> -3x = 6/5 + 3/4`
`=> -3x = 39/20`
`=> x = 39/20 : -3`
`=> x = -13/20`
Vậy `x =-13/20`
`b, 1/7 - 3/5x = 3/5`
`=> 3/5x = 1/7 - 3/5`
`=> 3/5x = -16/35`
`=> x = -16/35 : 3/5`
`=> x = -16/21`
Vậy `x =-16/21`
a: \(-3x-\dfrac{3}{4}=\dfrac{6}{5}\)
=>\(-3x=\dfrac{3}{4}+\dfrac{6}{5}=\dfrac{15}{20}+\dfrac{24}{20}=\dfrac{39}{20}\)
=>\(x=\dfrac{39}{20}:\left(-3\right)=-\dfrac{13}{20}\)
b: \(\dfrac{1}{7}-\dfrac{3}{5}x=\dfrac{3}{5}\)
=>\(\dfrac{3}{5}x=\dfrac{1}{7}-\dfrac{3}{5}=\dfrac{5}{35}-\dfrac{21}{35}=-\dfrac{16}{35}\)
=>\(x=-\dfrac{16}{35}:\dfrac{3}{5}=-\dfrac{16}{35}\cdot\dfrac{5}{3}=\dfrac{-16}{21}\)
c: \(\dfrac{3}{7}-\dfrac{1}{2}x=\dfrac{5}{3}\)
=>\(\dfrac{1}{2}x=\dfrac{3}{7}-\dfrac{5}{3}=\dfrac{9}{21}-\dfrac{35}{21}=-\dfrac{26}{21}\)
=>\(x=-\dfrac{26}{21}\cdot2=-\dfrac{52}{21}\)
d: \(-\dfrac{2}{3}x+2=\dfrac{3}{4}\)
=>\(-\dfrac{2}{3}x=\dfrac{3}{4}-2=-\dfrac{5}{4}\)
=>\(x=\dfrac{5}{4}:\dfrac{2}{3}=\dfrac{5}{4}\cdot\dfrac{3}{2}=\dfrac{15}{8}\)